Trace metals (Fe, Mn, Zn, Cu) in the polychaete Americonuphis reesei (Class: Polychaeta), in El Salado Beach, Aguadulce, Panamá - Rodríguez, Diana (2020)
The concentration of the heavy metals Fe, Mn, Zn, and Cu was determined in a homogenized sample of the polychaete Americonuphis reesei tissue in three sampling stations in Playa El Salado, Parita Bay, during the dry season in 2017. Three sampling locations were established at each station, 50 m apart from each other. Samples were digested with nitric acid, and metal concentration was determined by atomic absorption spectrophotometry. The highest concentration recorded was Fe, with an average of 581.98 µg·gˉ¹, followed by Mn with 25.71 µg·gˉ¹. The lowest values were reported for Zn, 16.05 µg·gˉ¹ and Cu, 3.52 µg·gˉ¹. A significant correlation was found between Fe and Mn (r = 0.95) and Mn and Cu (r = 0.71) P <0.01 as well as a highly significant correlation between Fe and Cu (r = 0.64) P <0.002. The sizes of polychaetes in stations 1 (Rio Santa María) and 3 (Palo Blanco) show no significant differences; however, sizes in station 2 (El Playón) showed differences compared to the other two stations. No correlation was found between length and metal concentration. Metal concentrations between the stations indicate that there is a significant difference in Mn and Fe in stations 1 and 3, and in Fe between stations 1 and 2. Metals detected in the tissue do not pose any risk since the concentrations are below the values of the established standards.